2016
DOI: 10.1021/acs.joc.6b01905
|View full text |Cite
|
Sign up to set email alerts
|

Sequential One-Pot Multienzyme Chemoenzymatic Synthesis of Glycosphingolipid Glycans

Abstract: Glycosphingolipids are a diverse family of biologically important glycolipids. In addition to variations on the lipid component, more than 300 glycosphingolipid glycans have been characterized. These glycans are directly involved in various molecular recognition events. Several naturally occurring sialic acid forms have been found in sialic acid-containing glycosphingolipids, namely gangliosides. However, ganglioside glycans containing less common sialic acid forms are currently not available. Herein, highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
100
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 83 publications
3
100
0
Order By: Relevance
“…Ganglioside GM1 is a glycan epitope located on the cell surface and plays important roles in many biological processes such as virus-cell interactions. [24] The enzymatic synthesis of GM1 from lactose involves three glycosylation steps. [24] The enzymes used are Pasteurella multocida α2,3-sialyltransferase (PmsT1), Campylobacter jejuni β1,4-N-acetylgalactosaminyltransferase (CgtA) and Campylobacter jejuni β1,3-galactosyltransferase CgtB.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ganglioside GM1 is a glycan epitope located on the cell surface and plays important roles in many biological processes such as virus-cell interactions. [24] The enzymatic synthesis of GM1 from lactose involves three glycosylation steps. [24] The enzymes used are Pasteurella multocida α2,3-sialyltransferase (PmsT1), Campylobacter jejuni β1,4-N-acetylgalactosaminyltransferase (CgtA) and Campylobacter jejuni β1,3-galactosyltransferase CgtB.…”
mentioning
confidence: 99%
“…[24] The enzymatic synthesis of GM1 from lactose involves three glycosylation steps. [24] The enzymes used are Pasteurella multocida α2,3-sialyltransferase (PmsT1), Campylobacter jejuni β1,4-N-acetylgalactosaminyltransferase (CgtA) and Campylobacter jejuni β1,3-galactosyltransferase CgtB. [24] The standardized procedure contains three processes (Figure 4B): automated synthesis, product release, and product purification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively low yield was due to GalβSEt ( 17 ) being a less optimal acceptor than GalNAcβOR in GM2 or GD2 ganglioside oligosaccharides. 34 …”
Section: Resultsmentioning
confidence: 99%
“…[6] By treating NK cells with sialidase to remove NeuAc and disrupt the cis interactions,t he unmasked Siglec-7 can interact with DSGb5-Cer on the surface of the human renal cancer cell line ACHN,decreasing the cytotoxicity of the NK cells and promoting the metastasis and invasion of RCC. [8] Obtaining as ufficient amount of pure DSGb5 is key to elucidating its mechanism of action and to further develop cancer immunotherapies.C larifying the binding activities of sialylated globo-series glycans and the effect of the NeuAc position on their interactions with Siglec-7 is also of great interest.Thee nzymatic and chemoenzymatic syntheses of globoseries glycans,such as Gb5, SSEA-4, and Globo H, have been reported by several research groups, [9][10][11] but no method has been reported for the synthesis of DSGb5. DSGb5 has aunique glycan structure with two NeuAcs as a2,3-and a2,6linkages on the nonreducing-end galactose (Gal) and Nacetylgalactosamine (GalNAc), respectively,o fG b5 (Figure 1).…”
mentioning
confidence: 99%